Complex interactions in aqueous PIL-PNIPAm-PIL triblock copolymer solutions. (10th February 2015) - Karjalainen, Erno; Khlebnikov, Vitaliy; Korpi, Antti; Hirvonen, Sami-Pekka; Hietala, Sami; Aseyev, Vladimir; Tenhu, Heikki
Abstract: Triblock copolymers with a poly(N-isopropyl acrylamide) (PNIPAm) central block and short cationic polymeric ionic liquid (PIL) endblocks were synthesized via ATRP. The chemically different blocks interact with each other and thus the presence and length of the PIL blocks affected the aggregation behavior of the thermoresponsive polymers at temperatures below and above the cloud point. The PIL-PNIPAm interactions decreased the enthalpy of phase separation at the cloud point not only in the case of block copolymers but also in mixtures of corresponding homopolymers. However, the decrease in ΔH was not directly proportional to the number of IL units present. This indicates that the IL units do not solely complex with the NIPAm units, but the PILs also interact with each other. The morphology of the aggregates is different with different lengths of the PIL blocks. At higher concentrations the block copolymers formed stable gels upon heating due to the phase transition of PNIPAm and the solubilizing effect of the PIL blocks. Graphical abstract: Highlights: PIL-PNIP Am-PIL triblock copolymers were synthesized. Complex interactions between collapsed polymers. The aggregate structure is very much dependent on the length of the PIL-block. Concentrated solutions form gels upon heating. Also, the respective homopolymers interact in mixed solutions.